Integrated Care for Older People with Different Frailty Levels: A Qualitative Study of Local Implementation of a National Policy in Luton, England - Nimra Khan; Gurch Randhawa; David Hewson (International Journal of Integrated Care, 2023)
Introduction: The NHS England General Medical Services 2017–18 contract made it mandatory for general practices in England to identify and manage older people proactively. In response to the national policy, the Luton Framework for Frailty (LFF) programme was developed to target older residents of Luton and offer interventions according to their frailty level. The aim of this study was to gain a deeper understanding of the LFF and the factors that affect the implementation of a proactive integrated care service for older people with different frailty levels (OPDFL). Methods: We undertook document analyses and conducted semi-structured interviews with stakeholders to create a ‘thick description’ that provides insights into the LFF. Results: Healthy ageing interventions bring beneficial outcomes but to increase the uptake they should be co-produced with older people. A common electronic system within primary care and multidisciplinary team meetings (MDT) aid implementation. However, variation in implementation across Luton, different levels of buy-in for MDT, and different data systems in primary and secondary care make implementation challenging. Conclusion: The LFF is a promising initiative and lessons learned are likely to be transferable to other settings as proactive management of frailty takes on greater policy prominence in the UK and worldwide.